(untitled) (Journal of Partial Differential Equations, 2001)
We study the Lime-asymptotic behavior of solutions to general Navier-Stokes equations in even and higher than two space-dimensions. Through the pointwise estimates of the Green function of the linearized system, we obtain expressions of the time-asymptotic behavior of the solutions. The result coincides with weak Huygan's principle.